SYNTHESIS, CHARACTERIZATION AND PRELIMINARY ANTIMICROBIAL EVALUATION OF NEW SCHIFF BASES OF AMPICILLIN AND AMOXICILLIN DERIVED FROM ISATIN DERIVATIVES - Jawad Al-mudhafar, May Mohammed (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objectives: Six different Schiff bases were synthesized from ampicillin and amoxicillin with isatin, 5-bromoisatin, and 5-nitroisatin. Methods: Ampicillin and Amoxicillin are linked directly through their Î±-amino groups to the acyl side chain with isatin and isatin derivatives by nucleophilic addition using glacial acetic acid as a catalyst. Results: chemical structures of these Schiff bases were confirmed using FTIR, 1H NMR and elemental microanalysis. The antibacterial activity was evaluated by measuring minimum inhibitory concentration (MIC) values and showed various degrees of antibacterial activities when compared with parent drugs. Compounds 1a and 2b, which are the Schiff bases of ampicillin and amoxicillin with isatin, showed very significant activity against methicillin-resistant Staphylococcus aureus (MRSA). Moreover, Schiff bases with 5-bromoisatin (1b and 2b) displayed significant activity against MRSA and less activity against Staphylococcus aureus (S. aureus). Conclusion: The new Schiff bases of isatin and 5-bromoisatin linked to ampicillin and amoxicillin showed interesting antibacterial activities. Keywords: Ampicillin, Amoxicillin, Schiff bases, Isatin derivatives